Politicising the study of sustainable living practices - Knott, Janice Denegri; Nixon, Elizabeth; Abraham, Kathryn (Taylor & Francis, 2018)
In studies of consumption, social theories of practice foreground the purchasing and use of resources not for intrinsic pleasure but rather in the routine accomplishment of ‘normal’ ways of living. In this paper we argue that a key strength of theories of practice lies in their ability to expose questions of power in the construction of normality, but that this has been largely overlooked. Since practice theories are leveraged in understanding urgent questions of climate change, we use ethnographic data of a sustainable community in England to examine the normative dimension of sustainability. Using Michel Foucault’s approach to practice, we elucidate the social technologies operating in the community that govern sustainable practices in the absence of a singular cultural authority. We illustrate how shared understanding guiding normative sustainable practice was negotiated and maintained through collective ethical work, the paramount importance of interpersonal harmony, and the continual formation of ethical subjects.